Mutagenicity of quindoxin, its metabolites, and two substituted quinoxaline-di-N-oxides. - Beutin, L (1981)
The quinoxaline-di-N-oxides carbadox, olaquindox, and quindoxin, which are potent antibacterial agents, were tested for mutagenicity in the Salmonella microsomal system. They all induced base pair substitutions and frameshift mutations in Salmonella, and occurred independently of the presence of a rat liver microsomal fraction in the test system. Mutagenicity was dependent on the presence of their N-oxide groups, since quinoxaline, a completely reduced derivative of quindoxin, was not mutagenic, whereas the partially reduced quinoxaline-N-oxide exhibited a lower mutagenic activity than quindoxin. recA and uvrB Salmonella were found to be more susceptible to mutagenic quinoxaline derivatives than wild-type strains. The mutagenicity of quinoxaline-di-N-oxides was enhanced under anaerobic incubation as was the antibacterial activity. These results suggest that both the antibacterial and mutagenic activity of quinoxaline-di-N-oxides depend upon the same bacterial activation mechanism.